Environmental Reconstruction and Tracking as Methods to Explore Social Interactions in Marine Environments: A Test Case With the Mediterranean Rainbow Wrasse Coris julis - Goverts, Zoë; Nührenberg, Paul; Jordan, Alex (Frontiers in Marine Science, 2021)
A key aspect of understanding social interactions in marine animals is determining whether individuals freely interact in fission-fusion groups, or have spatially structured interactions, for example territories or home ranges. Territoriality can influence access to mates, food resources, or shelter sites, and may also impact conservation efforts, as the delineation of marine protected areas relies on knowledge of home ranges and movement patterns. However, accurately determining distribution and movement is challenging for many marine species, especially small and medium species, which cannot carry beacons or tags to automatically measure movement, and are also difficult for human observers to accurately follow. Yet these smaller species comprise the bulk of near-shore assemblages, and are essential conservation targets. As such, novel solutions for monitoring movement and behavior are required. Here we use a combination of tracking and environmental reconstruction to explore territoriality, aggression, and navigation in a small marine fish, explicitly applying this technique to questions of sociality in the marine environment. We use the Mediterranean Rainbow Wrasse, Coris julis, as a test case, but this approach can be extended to many other species and contexts. In contrast with previous reports for this species, we find that during our observation period, female C. julis occupy consistent territories over sand patches, and that they defend these territories against same-sex conspecifics. Displacement experiments revealed two further important social behavioral traits – first that displaced individuals were able to navigate back to their territory, avoiding almost all other female territories as they returned. Second that when displaced fish approached the territories of others, residents of these territories were often aggressive to the non-neighboring fish, in contrast with our observations of low aggression counts toward their natural neighbors. Resident fish therefore appear to show differing levels of aggressiveness depending on their social relationship with same-sex conspecifics. Overall, these results suggest a sophisticated degree of social behavior in this marine wrasse, dependent on social and structural environment, but which can only effectively be revealed by state-of-the-art tracking and environment reconstruction techniques.